APPLICATION OF NANO SOFTENERS ON 97% / 3% COTTON/LYCRA FABRICS KNITTED BY VORTEX AND RING SPUN YARNS - (:unkn) unknown (NATL RES & DEVELOP INST TEXTILES & LEATHER, 2010)
Nowadays, nano softeners are widely used in the textile industry. In this work, 97%/3% cotton/Lycra fabrics knitted by Vortex and ring spun yarns were pre-treated and later exhaust dyed by the reactive dyes, namely C.I. Reactive Yellow 160, C.I. Reactive Red 180 and C.I. Reactive Blue 181. The fabrics dyed were treated by three nano softeners, namely Perisoft Nano (Dr. Petry), Microsilk EG Super (Organik Kimya), and Sebosan 100 (Bozetto), as well as a cationic softener, Persoftal AKS (Lanxess). The dyed fabrics were finally evaluated by the colour change, fastness properties, colour difference, softness, crease recovery and pilling properties, in respect to the applied nano softeners. By the application of the nano softeners, fabrics with good colour fastnesses, less colour change and less change in the hue angle, very good' crease recovery and very good handle properties were achieved.
Keywords: nano softeners; Vortex yarn; cotton/Lycra blends; reactive dyeing; VARIABLES